Answer:
Step-by-step explanation:
-3a + 6b = a + 4b
-4a + 6b = 4b
-4a = -2b
a = -2b/-4
f(a) = -b/2
Answer:
The Answer is: y = 2x - 3
Step-by-step explanation:
Given points: (3, 3) and (4, 5)
Find the slope, m:
m = y - y1/(x - x1)
m = 3 - 5/(3 - 4)
m = -2/-1 = 2
Use the Point Slope form of the equation:
y - y1 = m(x - x1)
y - 5 = 2(x - 4)
y - 5 = 2x - 8
y = 2x - 8 + 5
y = 2x - 3
Proof:
f(3) = 2(3) - 3
= 6 - 3 = 3, giving (3, 3)
Answer:
B.6
Step-by-step explanation:
f(2)=(2+1)2
=(3) 2
=6
Answer:
yes
Step-by-step explanation:
Answer:
168 in²
Step-by-step explanation:
The square would be 36 in²
Area of a triangle is A= 1/2 bh
A = 1/2 (11 x 6), A= 1/2 (66)
1/2 (66) = 33 in², which is the area of a triangle.
Then you multiply 33 x 4 to get the area of all the triangles, which is 132 in²
You add the area of the square to the area of the triangles, which is 168 in².